Matlab-Based Design Consideration of Series ZVS Single-Ended Resonant DC-DC Converter - Nikolay Hinov; Bogdan Gilev (Mathematics, 2023)
The paper presents a model-based design consideration of a series single-ended transistor resonant DC-DC converter with zero voltage switching (ZVS). A characteristic of this converter is that it is highly efficient due to the resonant nature of electromagnetic processes in the power circuit and operation with soft commutations. The manuscript proposes that the determination of some of the circuit elements of the device be carried out with optimization procedures based on the application of artificial intelligence techniques. For this purpose, an objective function is used with additional constraints, such as equalities and inequalities, for both the optimization parameters and the state variables. The use of the proposed method is justified in cases where there is no methodology for the design of the specific power electronic device or there is, but it is too complicated to apply. This is usually due to the increasing complexity of power circuits and their possible modes of operation and the inevitable assumptions and limitations in the analysis and the relevant methodologies based on that analysis. In this way, a natural combination, complement and development of classical design methods with innovative ones based on the application of artificial intelligence techniques is carried out.